Biomimicking Bone–Implant Interface Facilitates the Bioadaption of a New Degradable Magnesium Alloy to the Bone Tissue Microenvironment. Issue 23 (28th October 2021) - Li, Wenting; Qiao, Wei; Liu, Xiao; Bian, Dong; Shen, Danni; Zheng, Yufeng; Wu, Jun; Kwan, Kenny Y. H.; Wong, Tak Man; Cheung, Kenneth M. C.; Yeung, Kelvin W. K.
Abstract: The most critical factor determining the success of biodegradable bone implants is the host tissue response, which greatly depends on their degradation behaviors. Here, a new magnesium‐based implant, namely magnesium–silicon–calcium (Mg–0.2Si–1.0Ca) alloy, that coordinates its biodegradation along with the bone regenerative process via a self‐assembled, multilayered bone–implant interface is designed. At first, its rapid biocorrosion contributes to a burst release of Mg 2+, leading to a pro‐osteogenic immune microenvironment in bone. Meanwhile, with the simultaneous intervention of Ca and Si in the secondary phases of the new alloy, a hierarchical layered calcified matrix is rapidly formed at the degrading interface that favored the subsequent bone mineralization. In contrast, pure Mg or Mg–0.2Si alloy without the development of this interface at the beginning will unavoidably induce detrimental bone loss. Hence, it is believed this biomimicking interface justifies its bioadaptability in which it can modulate its degradation in vivo and accelerate bone mineralization. Abstract : The spontaneously formed degradation layers at the bone–implant interface are the key to the superior performance of Mg–Si–Ca alloy, as they regulate the biodegradation behaviors of the implant to elicit an appropriate host response at different stages of bone healing.